The effect of air purification on liquid air energy storage – An analysis from molecular to systematic modelling. (15th October 2021) - Wang, Chen; Zhang, Xiaosong; You, Zhanping; Zhang, Muxing; Huang, Shifang; She, Xiaohui
Highlights: Liquid air energy storage (LAES) is studied from molecular to systematic scales Effect of air purification on the LAES system is investigated Exhaust air rather than external energy is suggested to regenerate air purification The novel air purification improves round trip efficiency of the LAES by 2.3% The proposed LAES shows a round trip efficiency of 59.6% and CHP efficiency of 86.7% Abstract: Liquid air energy storage (LAES) is regarded as one of the most promising large-scale energy storage technologies due to its unique advantages of high energy storage density, no geographical constraints and long life-span. The LAES mainly includes air liquefaction (charging cycle) at off-peak time and power generation (discharging cycle) at peak time. During air liquefaction, ambient air is first required to remove its compositions with high freezing points (H2 O and CO2 ) before it is cooled down (denoted as air purification process), preventing pipeline blockage and guaranteeing safe operation. However, most of previous studies simply neglected the air purification process and assumed ambient air was already purified. This may cause overestimation of the LAES performance as the air purification process usually consumes thermal energy or electricity. To address this issue, this paper proposes a novel LAES system with energy-efficient air purification. Dynamic characteristics of the air purification process are investigated from molecular to systematic modeling for the first time. Simulation results show that the air purification process could be driven by exhaust air from the air turbine at peak time rather than thermal energy or electricity in the traditional methods. This could improve the electrical round trip efficiency by 2.3% compared with the traditional methods. In addition, the proposed LAES system shows a combined heat and power efficiency of 82.5-86.7%, an electrical round trip efficiency of 47.9-59.6% and an exergy efficiency of 58.4-68%. These findings will be helpful to understand the function of air purification in the LAES system, providing guidelines for practical applications.